Upaya Meningkatkan Kompetensi Profesional Guru - Hanifuddin Jamin (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
Teachers are positions or professions that require special skills, work as a teacher can not be done by someone without having expertise as a teacher. Being a teacher requires special requirements. What else if being a professional teacher then must have four competencies including: Pedagogic Competence, Personality Competence, Social Competence and Professional Competence. Professional Teachers Must Have Good Teaching Skills, Have Large Insights, Mastering Curriculum, Mastering the media of learning, Mastery of technology, Have a good personality and Be a good role model.